2021
DOI: 10.1021/acsomega.1c00736
|View full text |Cite
|
Sign up to set email alerts
|

π-Conjugated Trigonal Planar [C(NH2)3]+ Cationic Group: A Superior Functional Unit for Ultraviolet Nonlinear Optical Materials

Abstract: Employing π-conjugated anionic groups in molecular construction has been proven to be an effective strategy to find superior ultraviolet (UV) nonlinear optical (NLO) crystals over the decades. Herein, unlike the traditional π-conjugated anionic groups, we identify that a π-conjugated cationic group, viz., [C(NH 2 ) 3 ] + , is also an excellent UV NLO-active functional group in theory. Furthermore, we identify a [C(NH 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Recently, [C­(NH 2 ) 3 ] + (Gu) cationic groups with a planar π-conjugated triangular structure drew our attention. , It is found that the Gu cation has a wide range of UV transmission, which could replace alkali metal/alkaline earth metal cations to ensure the transmission of materials in the UV region. Moreover, its unique planar π-conjugated structure not only exhibits a large anisotropic polarizability, close to that of the classical BO 3 , NO 3 , and CO 3 anionic groups, but also acts as a good structure-directing template to tune the structure, because the linkage with the Gu cation could only extend along the C–N plane.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, [C­(NH 2 ) 3 ] + (Gu) cationic groups with a planar π-conjugated triangular structure drew our attention. , It is found that the Gu cation has a wide range of UV transmission, which could replace alkali metal/alkaline earth metal cations to ensure the transmission of materials in the UV region. Moreover, its unique planar π-conjugated structure not only exhibits a large anisotropic polarizability, close to that of the classical BO 3 , NO 3 , and CO 3 anionic groups, but also acts as a good structure-directing template to tune the structure, because the linkage with the Gu cation could only extend along the C–N plane.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, an organic π-conjugated [C­(NH 2 ) 3 ] group, as a new type of NLO-active FBUs, has attracted a great deal of research interest. , The [C­(NH 2 ) 3 ] (guanidine cation) group is analogous to the inorganic [BO 3 ] group, in which the central C atom links with three N atoms to create a planar configuration. Hence, it can be predicted that guanidine-based crystals may show a large band gap and optical anisotropic polarizability, and some experimental results have been reported, such as C­(NH 2 ) 3 ClO 4 , [C­(NH 2 ) 3 ] 3 PO 4 ·2H 2 O, BaGuCl 2 , and C­(NH 2 ) 3 SO 3 F . It has shown that the rational combination of two or more types of NLO-active FBUs can produce promising NLO crystals. ,, Therefore, it is interesting to develop guanidine-based NLO crystals by combining different functional moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the introduction of organic cation groups with structural diversities into material systems with inorganic anion groups has produced many superior organic–inorganic hybrid NLO materials, such as C(NH 2 ) 3 ClO 4 (3 × KDP), 40 [C(NH 2 ) 3 ] 6 (PO 4 ) 2 ·3H 2 O (3.8 × KDP) 41 and (C 5 H 6 ON) + (H 2 PO 4 ) − (3 × KDP) etc. 42 To our knowledge, only one case of an organic–inorganic hybrid NLO iodate has been studied, that is [ o -C 5 H 4 NHOH] 2 [I 7 O 18 (OH)]·3H 2 O (8.5 × KDP).…”
mentioning
confidence: 99%